Ảnh hưởng của thể chế quản trị địa phương tới tăng trưởng kinh tế cấp tỉnh ở Việt Nam - Lê Quang Cảnh; Đỗ Thị Tuyết Nhung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Recent stylized facts indicate that better local governance associates with higher economic growth. Using provincial data collected by the General Statistics Office and Vietnam Chamber of Commerce and Industry, this paper applies dynamic panel data regression models with two-step procedure to estimate impacts of provincial governance quality on economic growth. Estimated empirical results show that higher quality of provincial governance strongly associates with higher economic growth; different measures of the provincial governance quality have different effects on provincial economic growth; smaller provinces in terms of population size have higher impacts of the governance quality on economic growth. These results have shed the light on policy recommendations to improve quality of governance and its effects on provincial economic growth.
Keywords: Quality of governance; Institutions; Economic growth; Provincial level